Дискурс дихотомии духа и тела в философии протестантизма - Тесленко, Татьяна Викторовна (Грани, Днипро, 2017)
RU: На основе историко-философской реконструкции теоретических установок Реформации XVI-XVII вв. в контексте понимания специфики дихотомии духа и тела выявлено, что, стремясь возродить христианство в его первоначальной чистоте, реформаторы, поделив мир на духовный / трансцендентный и телесный / тварный, утверждают превосходство идеального духа как главное вместилище божественного присутствия. Заменяя внешнюю религиозность внутренней, философские положения Реформации также утверждают плюрализм, что, в свою очередь, привело к расколу единого реформационного движения. Опираясь на методологические возможности исследования онтологического дуализма обнаружено, что дихотомии «дух-материя» и «душа-тело» демонстрируют в протестантизме острый конфликт первого и второго членов оппозиции, именно в своей конфронтации представляют принцип субъективизации. И хотя реформаторы меньше всего стремились быть философами, самыми существенными последствиями их новых представлений стали выводы аксиологического и этического порядка, мощно повлиявшие на рецепцию в философии и культуре XVI-XVII вв. принципов «логики доминирования» в ценностно-иерархическом мышлении эпохи Реформации.

EN: Studying the dichotomy of «soul-body» in the protestant teaching showed that those practical conclusions that the reformators put high in their ideology, Descartes cast in the method of the «pure thought» which motes from the universal to the particular by means of the «pure reason» without any influence of the body. It is known, however, that this assumption does not correspond to Descartes’ later assertion of the unity of the reason and the body. Though many scientists claim that this opposition cannot be eliminated the recent tendency to solve their complicated relations is rather vivid. It is aimed at non-oppositional considering the dichotomy of «soul-body», disputing the claim that all the modes are lither absolutely mental or absolutely physical ones. It is proved that the protestant ethics was constructed on the ideals of the community; at the initial stage protestants stood for the interests of the majority of people, for the truth for everybody; their ethics had a mass character, that is why the Reformation historically turned out to be more supported by people than humanism, being oriented at the social and political realization. Hence the specific character of subjectivation at that period Asserting the thesis that man is unable to reach salvation by his own capabilities reformators by no means disrupt the link between salvation and morality. The problem lies in the fact that the moral ideal in the protestants teachings was unmeasurably high and not attainable «by definition» – Christ’s personality and extreme demands of the new Testament; simultaneously the verge between the freedom of the moral intuition and amoralism appears to be extremely thin. The faith does not secure man against a moral error, lust for the body does not disappear, «the damaged» nature of man does not change. The faith is realigned in «the voice» of the conscience, but listenery to it man inevitably «transcripts» the voice into the language of actions. Thus, proclaiming powerlessness of man, the Reformation proclaims the highest degree of the moral responsibility. The nationality of the modernity having refused the radical binarism of soul and body, enters into the opening «New World» of the anthropocentrism; Descartes claims that ethical norms should be considered in «the light of Reason», thus identifying moral virtues with reasoning. The paradox character of the Reformation teaching is also represented in the fact that its ideology, enhancing intolerance, asserts pluralism. The former position is directly connected with that «postmodern situation» that the western world is living through now.

UK: Вивчення теми «духу і тіла» в протестантизмі показало, що ті «практичні» висновки, які Реформатори звели в ранг своєї ідеології, у філософії Р. Декарта вилилися в метод «чистої думки», що рухається від універсалій до частковостей за допомогою «чистого розуму» без будь-якого впливу тіла. Проте, як відомо, це допущення не узгоджується із його пізнішим затвердженням союзу розуму й тіла в «Пристрастях душі». І хоча багато учених вважають, що ця бінарна опозиція не може бути елімінована, останніми роками виявляється тенденція до певного вирішення складних відносин між картезіанським дуалізмом і неопозиційним розглядом душі й тіла, кидаючи виклик твердженню, що всі модуси є або абсолютно ментальними, або абсолютно фізичними. У статті доводиться, що протестантизм стає провідною духовною течією свого часу, передусім, через свої ідеологічні установки: протестантська етика початкового етапу будувалася на ідеалах общинності, протестанти стояли за інтереси багатьох, за «правду для всіх», що, у свою чергу, відображало інтереси «третього стану» – бюргерства, яке представляє в той період свої інтереси як інтереси всіх членів суспільства. Виражаючи сподівання висхідної буржуазії, реформатори парадоксальним чином сполучають середньовічне світовідчуття із репрезентацією ідеології, що в класичній історіографії розглядається як прогресивна сила. Парадоксальність філософських положень Реформації полягає також у тому, що її ідеологія, підсилюючи нетерпимість, одночасно затверджує плюралізм. Останнє, наприклад, пов’язано з ситуацією постмодерну, яку переживає західний світ у наш час.
The Discourse of the Dichotomy of Spirit and Body in the Philosophy of Protestantism
Дискурс дихотомії духу і тіла в філософії протестантизму
Т. Тесленко: ORCID 0000-0002-5810-3569
Keywords: бюргерство; Библия; евангельская этика; Реформация; идеология; разум; дуализм; the burghers; Bible; the Gospel ethics; Reformation; idealism; reason; dualism; Біблія; євангельська етика; Реформація; ідеологія; розум; дуалізм; КЕМ